Relationships of post-stroke fatigue with mobility, recovery, performance, and participation-related outcomes: a systematic review and meta-analysis - Usman, Jibrin S.; Wong, Thomson W. L.; Ng, Shamay S. M. (Frontiers in Neurology, 2024)
Background: Effective post-stroke mobility, recovery, performance and participation are goals highly desired by every stroke survivor. However, such outcomes may be hindered by post-stroke fatigue (PSF) which can affect numerous components of post-stroke mobility, recovery, performance, functioning, community participation and return to work. This review was assessing the scientific evidence on the relationship of PSF with mobility function, functional recovery, functional performance and participation related outcomes among stroke survivors. Method: Cochrane Central, PubMed, Embase, and Web of Science (WoS) databases were searched for relevant studies from inception to December 2023. Observational, cross-sectional, and longitudinal studies were retrieved. The methodological quality of the included studies was assessed using the National Institute of Health’s quality assessment tool. Risk of bias was assessed using the quality in prognostic studies tool. Twenty-eight studies (n = 2495 participants, male = 1626, mean age [minimum= 52.5 ± 9.5 years, maximum= 71.1 ± 9.9 years]) were included. The data analysis was performed using narrative and quantitative synthesis. Fixed and random effects meta-analysis were performed to determine the relationships between PSF and outcomes of interest. Results: The results revealed that chronic PSF had significant negative correlations with mobility (meta r = -0.106, p < 0.001), balance performance (meta r = -0.172; 95%; p = 0.004); and quality of life (meta r = -0.647; p < 0.001); but significant positive correlations with stroke impairment (meta r = 0.144, p < 0.001), and disability (meta r=0.480, p<0.001). Additionally, exertion/acute PSF had significant negative correlations with walking economy (meta r = -0.627, p < 0.001) and walking endurance (meta r = -0.421, p = 0.022). The certainty of evidence was moderate for these relationships. Conclusion: Our findings indicate that higher PSF is associated with less mobility, less balance performance, low participation, greater disability and greater stroke impairment in stroke survivors. Future studies, especially prospective longitudinal and randomized controlled trials, are warranted to substantiate our findings.